Critical Observations of Gaseous Elemental Mercury Air‐Sea Exchange. Issue 8 (23rd August 2021) - Osterwalder, S.; Nerentorp, M.; Zhu, W.; Jiskra, M.; Nilsson, E.; Nilsson, M. B.; Rutgersson, A.; Soerensen, A. L.; Sommar, J.; Wallin, M. B.; Wängberg, I.; Bishop, K.
Abstract: Air‐sea exchange of gaseous elemental mercury (Hg 0 ) is not well constrained, even though it is a major component of the global Hg cycle. Lack of Hg 0 flux measurements to validate parameterizations of the Hg 0 transfer velocity contributes to this uncertainty. We measured the Hg 0 flux on the Baltic Sea coast using micrometeorological methods (gradient‐based and relaxed eddy accumulation [REA]) and also simulated the flux with a gas exchange model. The coastal waters were typically supersaturated with Hg 0 (mean ± 1 σ  = 13.5 ± 3.5 ng m −3 ; ca. 10% of total Hg) compared to the atmosphere (1.3 ± 0.2 ng m −3 ). The Hg 0 flux calculated using the gas exchange model ranged from 0.1–1.3 ng m −2 h −1 (10th and 90th percentile) over the course of the campaign (May 10–June 20, 2017) and showed a distinct diel fluctuation. The mean coastal Hg 0 fluxes determined with the two gradient‐based approaches and REA were 0.3, 0.5, and 0.6 ng m −2 h −1, respectively. In contrast, the mean open sea Hg 0 flux measured with REA was larger (6.3 ng m −2 h −1 ). The open sea Hg 0 flux indicated a stronger wind speed dependence for the Hg 0 transfer velocity compared to commonly used parameterizations. Although based on a limited data set, we suggest that the wind speed dependence of the Hg 0 transfer velocity is more consistent with gases that have less water solubility than CO2 (e.g., O2 ). These pioneering flux measurements using micrometeorological techniques show that more such measurements would improve our understanding of air‐sea Hg exchange. Key Points: Mean coastal Hg 0 fluxes measured with micrometeorological methods were similar to fluxes based on Hg 0 aq measurements (gas exchange model) The gas exchange model predicted Hg 0 emission with a noon peak but flux measurements had no diel peak and periods of Hg 0 uptake A cubic relationship between wind speed and the gas transfer velocity was indicated by a subset of the Hg 0 open sea flux measurements